African American Culture and Legal Discourse
XIII, 257 p.
Keywords: This work examines the experiences of African Americans under the law and how African American culture has fostered a rich tradition of legal criticism. Moving between novels, music, and visual culture, the essays present race as a significant factor within legal discourse. Essays examine rights and sovereignty, violence and the law, and cultural ownership through the lens of African American culture. The volume argues that law must understand the effects of particular decisions and doctrines on African American life and culture and explores the ways in which African American cultural production has been largely centered on a critique of law.